Assessment of Serum Magnesium Mean Levels at Pre- and Postmagnesium Sulfate Uptake for Eclampsia Prevention: A Cross-Sectional Study - Tuan Minh Vo; Du Van Tran; Dat Quoc Nguyen; Toan Thi Nguyen; Mo Ha Nguyen; Thanh Tan Nguyen; Liem Ba Le (International Journal of Hypertension)
Conclusion: There were no eclampsia incidents in patients with severe preeclampsia treated with a regimen of a loading dose of 4.5 g MgSO4 followed by a 1 g-hourly maintenance. Nevertheless, about 17% of participants achieved the desired threshold of 2 mmol/L, indicating a need for additional research to refine the loading and maintenance doses of MgSO4 for better management of severe preeclampsia in Vietnamese women.